Integration of DNA barcoding into an ongoing inventory of complex tropical biodiversity - Ratnasingham, S.; Hausmann, A.; Harvey, D.J.; Gauld, I.D.; Hebert, P.D.N.; Hall, J.P.W.; Hajibabaei, M.; Haber, W.A.; Franclemont, J.G.; Espinoza, B.; Epstein, M.E.; Deans, A.R.; et al. (2009)
Inventory of the caterpillars, their food plants and parasitoids began in 1978 for today's Area de Conservacion Guanacaste (ACG), in northwestern Costa Rica. This complex mosaic of 120 000 ha of conserved and regenerating dry, cloud and rain forest over 0-2000 m elevation contains at least 10 000 species of non-leaf-mining caterpillars used by more than 5000 species of parasitoids. Several hundred thousand specimens of ACG-reared adult Lepidoptera and parasitoids have been intensively and extensively studied morphologically by many taxonomists, including most of the co-authors. DNA barcoding - the use of a standardized short mitochondrial DNA sequence to identify specimens and flush out undisclosed species - was added to the taxonomic identification process in 2003. Barcoding has been found to be extremely accurate during the identification of about 100 000 specimens of about 3500 morphologically defined species of adult moths, butterflies, tachinid flies, and parasitoid wasps. Less than 1% of the species have such similar barcodes that a molecularly based taxonomic identification is impossible. No specimen with a full barcode was misidentified when its barcode was compared with the barcode library. Also as expected from early trials, barcoding a series from all morphologically defined species, and correlating the morphological, ecological and barcode traits, has revealed many hundreds of overlooked presumptive species. Many but not all of these cryptic species can now be distinguished by subtle morphological and/or ecological traits previously ascribed to 'variation' or thought to be insignificant for species-level recognition. Adding DNA barcoding to the inventory has substantially improved the quality and depth of the inventory, and greatly multiplied the number of situations requiring further taxonomic work for resolution.